Rancang Bangun Sistem Social Campaign 'Relawanku' dengan Penerapan Agile Development untuk Optimalisasi Pengelolaan Kampanye Sosial - Haviv, Muhammad; Voutama, Apriade (Universitas Komputer Indonesia, 2025)
Digitalization has enhanced the effectiveness of social campaign management, including volunteer coordination and donation processing. This study develops Relawanku, a web-based system designed to optimize social campaign management. The system was built using the Agile Development method with the Scrum framework, enabling flexible and user-responsive development. Relawanku features campaign management, volunteer registration, and a digital donation system integrated with Midtrans. It utilizes React.js for the user interface and Golang for the backend, with JSON Web Token (JWT) authentication to enhance security. Evaluation results show improved efficiency in campaign management and increased transparency in donation transactions. This system allows social organizations to manage campaigns more effectively, boost volunteer engagement, and expand donation reach.